LEMBAGA JUDICIAL REVIEW UNDANG-UNDANG TERHADAP UNDANG-UNDANG DASAR : PERBANDINGAN ANTARA KEWENANGAN MAHKAMAH KONSTITUSI KOREA SELATAN DENGAN MAHKAMAH KONSTITUSI REPUBLIK INDONESIA - Atja Sulandra, Joseph; Roy Sumahardika, Anak Agung Ngurah (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2016)
This study aimed to compare the profile and authority of the Constitutional Court of South Korea with the Constitutional Court of the Republic of Indonesia, which is granted by its Constitution and related laws. The aim is to see how far the role of the Constitutional Court of the Republic of Indonesia as an institution of judicial review, so that it can also note the advantages and disadvantages in its function as the guardian of the constitution. Penelitian ini bertujuan untuk membandingkan profil dan kewenangan Mahkamah Konstitusi Korea Selatan dengan Mahkamah Konstitusi Republik Indonesia, yang diberikan oleh Undang-Undang Dasar serta Undang-Undang terkait. Tujuannya adalah untuk melihat seberapa jauh peran Mahkamah Konstitusi Republik Indonesia sebagai Lembaga Judicial Review Undang-undang terhadap Undang-Undang Dasar, sehingga dapat dilihat kelebihanan dan kekurangannya masing-masing dalam fungsinya sebagai lembaga pengawal konstitusi.
Keywords: Constitutional Court; the Constitutional Court of the Republic of Indonesia; Mahkamah Konstitusi; Mahkamah Konstitusi Republik Indonesia